CSR as a mediating to company characteristic, corporate governance, and firm value - Dewi, Hayuningtyas Pramesti; Uzliawati, Lia; Lestari, Tri; Ibrani, Ewing Yuvisa (Edelweiss Applied Science and Technology, 2024)
Investors use the company's value as a benchmark to assess financial performance. Therefore, we must conduct research that uncovers factors capable of enhancing the company's value. Moreover, the majority of research conducted to date has primarily focused on direct testing. This research aims to explain the mechanism of comprehending factors in generating company value based on the signaling theory framework. This study investigates the effect of corporate social responsibility (CSR) practices, as well as mediators such as profitability and size, on firm value in manufacturing firms that have listed their shares on the Indonesia Stock Exchange (BEI). The data analysis was performed using the EViews application based on the collected sample of companies in the period 2019–2022. The results of this research indicate that the level of profitability, company size, and corporate governance effect firm value components directly. This study also suggests that, in line with the signaling theory stream of research, corporate social responsibility (CSR) acts as an important channel to bind the profitable and large-sized firms along with governance mechanisms through the utilization of signals by investors about influential variables such as profitability levels or company size; overall governance practices enacted.